ChemInform Abstract: A General, Effcient and Green Procedure for Synthesis of Dihydropyrimidine‐5‐carboxamides in Low Melting Betaine Hydrochloride/Urea Mixture. Issue 44 (13th October 2016) - Liu, Peng; Hao, Jianwu; Zhang, Zhanhui
Abstract: A new, environment‐friendly protocol is described for the synthesis of dihydropyrimidine‐5‐carboxamides in a low‐melting deep eutectic solvent from a mixture of betaine hydrochloride with urea.